Observation of pregnancy outcomes in patients with hysteroscopic resection on submucous myomas. Issue 2 (12th December 2021) - Yang, Yeping; Yang, Yisai; You, Min; Chen, Lan; Sun, Feng
Abstract: Objective: The aim of this study was to assess postoperative pregnancy outcomes in patients with different types of submucous myomas after hysteroscopic resection. Materials and Methods: This retrospective unicentric study used data from the electronic medical records system of the hospital. All patients ( n  = 77) who underwent hysteroscopy for submucous myomas between November 2010 and December 2018 were included. Patients were divided into three groups according to the myoma classification (G0, G1, and G2). Medical files were reviewed and phone questionnaires were conducted to evaluate demographic characteristics, clinical features, surgical treatment, and pregnancy outcomes. Results: The median age of the patients was 32 (30.0, 34.0) years. The myoma diameter was 2.9 (2.0, 3.8) cm. The operation duration was 50.0 (30.0, 75.0) min. There were 15 patients in Group G0, 20 patients in Group G1, and 37 patients in Group G2. Follow‐up data were available for 65 of the 77 patients. The total pregnancy rate was 58 (89.2%) of 65. The live birth rate was 41 (70.7%) of 58. There was no significant difference in pregnancy rate (G0 100% vs. G1 76.5% vs. G2 91.2%; p  = 0.097) or in live birth rates among the three groups (G0 78.6% vs. G1 53.8% vs. G2 74.2%; p  = 0.325). Conclusion: There was no difference in pregnancy outcome among the three types of submucosal myomas. Our results support the idea that hysteroscopic myomectomy is an effective option for submucous myomas with good long‐term pregnancy outcomes.